Distribution of 2,4-Diacetylphloroglucinol Biosynthetic Genes among the Pseudomonas spp. Reveals Unexpected Polyphyletism - Almario, Juliana; Bruto, Maxime; Vacheron, Jordan; Prigent-Combaret, Claire; Moënne-Loccoz, Yvan; Muller, Daniel (Frontiers in Microbiology, 2017)
Fluorescent pseudomonads protecting plant roots from phytopathogens by producing 2,4-diacetylphloroglucinol (DAPG) are considered to form a monophyletic lineage comprised of DAPG+ Pseudomonas strains in the ‘P. corrugata’ and ‘P. protegens’ subgroups of the ‘Pseudomonas fluorescens’ group. However, DAPG production ability has not been investigated for many species of these two subgroups, and whether or not the DAPG+ Pseudomonas are truly monophyletic remained to be verified. Thus, the distribution of the DAPG biosynthetic operon (phlACBD genes) in the Pseudomonas spp. was investigated in sequenced genomes and type strains. Results showed that the DAPG+ Pseudomonas include species of the ‘P. fluorescens’ group, i.e. P. protegens, P. brassicacearum, P. kilonensis and P. thivervalensis, as expected, as well as P. gingeri in which it had not been documented. Surprisingly, they also include bacteria outside the ‘P. fluorescens’ group, as exemplified by Pseudomonas sp. OT69, and even two Betaproteobacteria genera. The phl operon-based phylogenetic tree was substantially congruent with the one inferred from concatenated housekeeping genes rpoB, gyrB and rrs. Contrariwise to current supposition, ancestral character reconstructions favored multiple independent acquisitions rather that one ancestral event followed by vertical inheritance. Indeed, based on synteny analyses, these acquisitions appeared to vary according to the Pseudomonas subgroup and even the phylogenetic groups within the subgroups. In conclusion, our study shows that the phl+ Pseudomonas populations form a polyphyletic group and suggests that DAPG biosynthesis might not be restricted to this genus. This is important to consider when assessing the ecological significance of phl+ bacterial populations in rhizosphere ecosystems.